Asymmetric shocks among U.S. states - Marco Del Negro (Federal Reserve Bank of Atlanta, 2000)
This paper applies a factor model to the study of risk sharing among U.S. states. The factor model makes it possible to disentangle movements in output and consumption due to national, regional, or state-specific business cycles from those due to measurement error. The results of the paper suggest that some findings of the previous literature which indicate a substantial amount of interstate risk sharing may be due to the presence of measurement error in output. When measurement error is properly taken into account, the evidence points towards a lack of interstate smoothing.
Keywords: 330; Consumption (Economics); Business cycles